Two-step ranging based on energy detection for IR-UWB sensor networks - ZHANG Ting-ting1; ZHANG Qin-yu2; ZHANG Nai-tong1 (Tongxin xuebao)
In order to design a low computational and cost ranging method for the IR-UWB （impulse radio ultra wideband） wireless sensor network, a two-step DP （direct path） component TOA （time of arrival） estimation algorithm based on energy detection was proposed. The first step was to determine DP energy block in which located by GLRT （generalized likelihood ratio test）. During the second step, the refined position of DP within the detected block was obtained by ML （maximum likelihood） estimation. A mathematical error model was set up for the two-step method which was veri-fied by the simulation results, and system parameters that affected the performance were studied by analytical and numerical methods. The results, compared with traditional ranging methods, show that this method achieves relative high performance under low complexity conditions.